(untitled) (Bangladesh Journal of Agricultural Research, 2018)
This study examined the relative efficiency of producing of selected pulse crops in Bangladesh and their comparative advantage in international trade. To know the comparative advantage in production of selected pulse crops. The study have calculated net financial and economic profitability, nominal protection coefficient of output (NPCO), nominal protection coefficient of input (NPCI), effective protection co-efficient (EPC), private cost ratio (PCR), policy analysis matrix (PAM) and domestic resource cost (DRC). Data used in this study were collected through Household surveys from 300 sample farms located in 12 villages under 6 districts in Bangladesh for the period 2015 to 2016. The selected pulse crops i.e lentil, chickpea and mungbean cultivation at farm level is very much remunerative to its growers. The domestic-border price ratio of selected pulse crops indicates that domestic pulse production was taxed and consumers were subsidized. The border price of selected pulse crops at producer level was mostly higher than the domestic producer price indicating that there is a wide scope to cultivate pulse crops for import substitution in Bangladesh. Policy Analysis Matrix for selected pulse crops under import parity prices showed that revenue transfer (Tk -14,755/mt) was negative indicated that government policies affect negatively to the pulse producer. The input transfer (Tk -1108/mt) was also negative indicating that the government has implemented input subsidy policy to the crop sector to offset higher cost of production. The domestic factor transfer was positive (Tk 15,171/mt) indicating that opportunity costs of non-tradable inputs were lower than their market prices. Finally the net profit/net policy transfer (Tk -28,503/mt) was negative which means that, the producers earn less profit and cannot minimize loss under existing condition and vice-versa. This means that under free trade, producers could make more profit in contrast to the existing policy environment. The NPCO values less than one imply that policies do not provide nominal protection for the pulse producers. The findings based on the indicators of NPCO, NPCI, EPC and PCR conclude that the existing government policy environment tends to protect the interest of the pulse producers in agricultural sector at production level. DRC results indicated that Bangladesh had comparative advantage of producing pulse crops and production of pulse crops would be highly efficient for import substitution. Bangladesh J. Agril. Res. 43(1): 109-123, March 2018